Food safety assessment and toxicity study of the synbiotic consortium SBD111. (October 2022) - Easson, D. Davidson; Murphy, Vincent A.; Ballok, Alicia E.; Soto-Giron, Maria J.; Schott, Eric M.; Rodricks, Joseph; Toledo, Gerardo V.
Abstract: The human gut microbiome plays a crucial role in skeletal homeostasis. The synbiotic consortium or Defined Microbial Assemblage™ (DMA™) food product, SBD111, consisting of probiotic microbes and prebiotic fibers was designed to promote bone health based on its capacity to produce short chain fatty acids (SCFA), the presence of genes for vitamin K2 production, and its ability to degrade plant fibers. A 28-day repeated administration study was performed to evaluate the oral toxicity of SBD111 in female rats (age/weight at study start: 5–7 weeks/120–180 g) administered levels of 0, 2.0 x 10 10, 9.8 x 10 10, or 2.0 x 10 11 colony forming units (CFU)/kg-bw. No mortality or morbidity occurred during the study. There were no significant differences in body weights, hematology, serum chemistry, coagulation, organ weights, or food consumption in the test groups compared to the controls. Liver weight to body weight ratios were signficantly decreased at 9.8 x 10 10 CFU/kg-bw when compared to controls. No treatment related changes in motor activity, sensory stimuli, or grip strength were observed. Based on these findings, SBD111 administered to female rats has a no-observable adverse effect level (NOAEL) at the highest level tested of 2.0 x 10 11 CFU/kg-bw. Highlights: SBD111 is a consortium of probiotic microbes designed to promote bone health. SBD111 was evaluated in rats at 2.0 x 10 10, 9.8 x 10 10, or 2.0 x 10 11 CFU/kg-bw. Doses were equivalent to 2, 10, and 20x the human daily intake of 9.5 x 10 10 . Administration to female rats produced no adverse effects at the any dose tested. The no-observable adverse effect level (NOAEL) of SBD111 was 2.0 x 10 11 CFU/kg-bw.